DNA Logic Circuits for Cancer Theranostics. Issue 20 (7th March 2022) - Chen, Jing; Fu, Shengnan; Zhang, Chunyi; Liu, Huiyu; Su, Xin
Abstract: Cancer diagnosis and therapeutics (theranostics) based on the tumor microenvironment (TME) and biomarkers has been an emerging approach for precision medicine. DNA nanotechnology dynamically controls the self‐assembly of DNA molecules at the nanometer scale to construct intelligent DNA chemical reaction systems. The DNA logic circuit is a particularly emerging approach for computing within the DNA chemical systems. DNA logic circuits can sensitively respond to tumor‐specific markers and the TME through logic operations and signal amplification, to generate detectable signals or to release anti‐cancer agents. In this review, the fundamental concepts of DNA logic circuits are clarified, the basic modules in the circuit are summarized, and how this advanced nano‐assembly circuit responds to tumor‐related molecules, how to perform logic operations, to realize signal amplification, and selectively release drugs through discussing over 30 application examples, are demonstrated. This review shows that DNA logic circuits have powerful logic judgment and signal amplification functions in improving the specificity and sensitivity of cancer diagnosis and making cancer treatment controllable. In the future, researchers are expected to overcome the existing shortcomings of DNA logic circuits and design smarter DNA devices with better biocompatibility and stability, which will further promote the development of cancer theranostics. Abstract : Recent progress in cancer theranostics applications of DNA logic circuits is summarized. The strategies are discussed to show how to utilize cancer biomarkers to construct DNA logic circuits. Rich examples of DNA logic circuits in various scenarios are provided and deeply discussed including in vitro detection, cell surface and cytoplasmic biomarker identification, and stimuli‐triggered drug release.